Ethical and Clinical Aspects of Intensive Care Unit Admission in Patients with Hematological Malignancies: Guidelines of the Ethics Commission of the French Society of Hematology - Malak, Sandra; Sotto, Jean-Jacques; Ceccaldi, Joël; Colombat, Philippe; Casassus, Philippe; Jaulmes, Dominique; Rochant, Henri; Cheminant, Morgane; Beaussant, Yvan; Zittoun, Robert; Bordessoule, Dominique (Advances in Hematology, 2014)
Admission of patients with hematological malignancies to intensive care unit (ICU) raises recurrent ethical issues for both hematological and intensivist teams. The decision of transfer to ICU has major consequences for end of life care for patients and their relatives. It also impacts organizational human and economic aspects for the ICU and global health policy. In light of the recent advances in hematology and critical care medicine, a wide multidisciplinary debate has been conducted resulting in guidelines approved by consensus by both disciplines. The main aspects developed were (i) clarification of the clinical situations that could lead to a transfer to ICU taking into account the severity criteria of both hematological malignancy and clinical distress, (ii) understanding the process of decision-making in a context of regular interdisciplinary concertation involving the patient and his relatives, (iii) organization of a collegial concertation at the time of the initial decision of transfer to ICU and throughout and beyond the stay in ICU. The aim of this work is to propose suggestions to strengthen the collaboration between the different teams involved, to facilitate the daily decision-making process, and to allow improvement of clinical practice.